Evaluation of the lignocellulose degradation potential of Mediterranean forests soil microbial communities through diversity and targeted functional metagenomics - Kalntremtziou, Maria; Papaioannou, Ioannis A.; Vangalis, Vasileios; Polemis, Elias; Pappas, Katherine M.; Zervakis, Georgios I.; Typas, Milton A. (Frontiers in Microbiology, 2023)
The enzymatic arsenal of several soil microorganisms renders them particularly suitable for the degradation of lignocellulose, a process of distinct ecological significance with promising biotechnological implications. In this study, we investigated the spatiotemporal diversity and distribution of bacteria and fungi with 16S and Internally Trascribed Spacer (ITS) ribosomal RNA next-generation-sequencing (NGS), focusing on forest mainland Abies cephalonica and insular Quercus ilex habitats of Greece. We analyzed samples during winter and summer periods, from different soil depths, and we applied optimized and combined targeted meta-omics approaches aiming at the peroxidase-catalase family enzymes to gain insights into the lignocellulose degradation process at the soil microbial community level. The microbial communities recorded showed distinct patterns of response to season, soil depth and vegetation type. Overall, in both forests Proteobacteria, Actinobacteria, Acidobacteria were the most abundant bacteria phyla, while the other phyla and the super-kingdom of Archaea were detected in very low numbers. Members of the orders Agaricales, Russulales, Sebacinales, Gomphales, Geastrales, Hysterangiales, Thelephorales and Trechisporales (Basidiomycota), and Pezizales, Sordariales, Eurotiales, Pleosporales, Helotiales and Diaporthales (Ascomycota) were the most abundant for Fungi. By using optimized “universal” PCR primers that targeted the peroxidase-catalase enzyme family, we identified several known and novel sequences from various Basidiomycota, even from taxa appearing at low abundance. The majority of the sequences recovered were manganese peroxidases from several genera of Agaricales, Hysterangiales, Gomphales, Geastrales, Russulales, Hymenochaetales and Trechisporales, while lignin- and versatile-peroxidases were limited to two to eight species, respectively. Comparisons of the obtained sequences with publicly available data allowed a detailed structural analysis of polymorphisms and functionally relevant amino-acid residues at phylogenetic level. The targeted metagenomics applied here revealed an important role in lignocellulose degradation of hitherto understudied orders of Basidiomycota, such as the Hysterangiales and Gomphales, while it also suggested the auxiliary activity of particular members of Proteobacteria, Actinobacteria, Acidobacteria, Verrucomicrobia and Gemmatimonadetes. The application of NGS-based metagenomics approaches allows a better understanding of the complex process of lignocellulolysis at the microbial community level as well as the identification of candidate taxa and genes for targeted functional investigations and genetic modifications.